Loving Each Other with the Concept of Hablumminannas in Hadith Perspective: A Study of Hadith Takhrij and Syarah - Suryana, Muhamad Aji (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss Abu Daud's Hadith No. 4290 regarding mutual compassion for humans (Hablumminannas) and all living things. It needs to be owned by everyone for the sake of a good life. This research applies a qualitative method through literature study with Takhrij and hadith commentary. The results of this study show that the quality of the hadith is considered sahih because it fulfills the conditions of a hadith that can be said to be sahih. From the commentary of the Hadith, it is known that this Hadith emphasizes to love each other among human beings (Hablumminannas), both in the form of loving, giving, respecting, appreciating and even forgiving mistakes. This study concludes that Islam has explained clearly through the verses of the Qur'an, one of which is reinforced by this hadith, and the example that has been set by the Prophet is an obligation as a human being that must be carried out. This study recommends further research on the hadith review of the attitude of loving and respecting others who are different in belief, race, and ethnicity so that it can be implemented in everyday life.